New Conditions for the Exponential Stability of Pseudolinear Difference Equations in Banach Spaces - Rigoberto Medina (Abstract and Applied Analysis)
We study the local exponential stability of evolution difference systems with slowly varying coefficients and nonlinear perturbations. We establish the robustness of the exponential stability in infinite-dimensional Banach spaces, in the sense that the exponential stability for a given pseudolinear equation persists under sufficiently small perturbations. The main methodology is based on a combined use of new norm estimates for operator-valued functions with the “freezing” method.